Pengembangan Aplikasi E-Learning dengan Fitur Penilaian Otomatis pada SMA Manda Elu - Diana Renda; Andreas Ariyanto Rangga; Emirensiana Dappa Ege (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
The application and utilization of technology in various fields is evidence that the development of technology is currently growing rapidly in the field. The field of education is one field that is not free from this development, as evidenced by the emergence of the concept of learning (E-learning). Electronic learning can be abbreviated as "e-learning." An online tool called e-learning allows teachers and students to collaborate in online classes. E-learning was developed to overcome the limitations of teachers and students, especially those related to time, location, conditions, and circumstances. Students can listen to what their teachers say without having to sit still in class thanks to e-learning. In addition, e-learning can reduce the amount of time allocated to study and, thus, reduce the costs associated with participation in studies or educational programs. It can be concluded based on the design of a web-based E-learning application at Manda Elu Private High School, supported by all the results of the questionnaires that have been filled out and assisted by the school's literature study: Here are some of the benefits of using e-learning applications: facilitating communication between teachers and students; helping students obtain learning materials; helping teachers and students in distributing assignments; this facilitates the exchange of information between schools and teachers; making it easier for teachers to process grades; and user-friendly because its implementation is web-based at SMA Swasta Manda Elu which is supported by all student results from completed assignments and literature studies available at the school. The e-learning application facilitates communication with students and teachers, helps students in obtaining learning materials, and helps teachers and students in dividing tasks. The e-learning application makes it easier for teachers and students to access information. The e-learning application makes it easier for teachers to give homework and students to get homework assignments. This e-learning application is easy to use.